Increased Levels of IL-17, IL-23, MIP-1α, MCP-1 and Global Leukocytes in Fibromyalgia Patients. Issue 3 (2nd October 2015) - Pernambuco, Andrei Pereira; Fonseca, Angélica Cristina Sousa; Oliveira, Gabriella Luciana de; Faria, Priscila Conceição; Silva, Raimisson Vieira; Meireles, Cecília; Arantes, Saulo Elyas; Silva, Fernanda Cristina; Reis, Débora d'Ávila
Abstract: Objectives: To evaluate and compare the blood leukocytes and plasmatic levels of cytokines [IL-17, IL-23, MIP-1α and MCP-1] found in patients with fibromyalgia [FM] and healthy controls. Methods: Forty-four women with FM and 28 healthy women matched by age and Body Mass Index [BMI] participated in this study. The white blood cell count was determined by the complete blood count [CBC]. The plasmatic levels of cytokines were determined by enzyme-linked immunosorbent assay [ELISA]. The statistical analysis was performed by means of the Kolmogorov–Smirnov test for data distribution, the Mann–Whitney test or independent t -test to test for intergroup differences, Spearman's correlation test for association between the variables and stepwise multiple regression to select the independent predictive variables. The tests were performed in SPSS v.19 (SPSS Inc., Chicago, IL), with significance level set to α = 0.05. Results: Patients with FM had significantly higher levels of global leukocytes, IL-17, IL-23, MIP-1α and MCP-1 than healthy controls. The absolute number of global leukocytes is directly and positively correlated with plasmatic levels of IL-17 and IL-23 in FM patients. IL-17 was the only variable selected in the prediction model of leukocyte levels in FM patients. Conclusions: The higher levels of global leucocytes, IL-17, IL-23, MIP-1α and MCP-1 showed by FM patients support the involvement of the immune system in the pathophysiology of this condition. The association between high levels of global leukocytes with high plasmatic levels of cytokines, mainly IL-17, in FM patients should be considered during the FM's diagnosis and clinical decision making.